Strategic Business Development Analysis Using the SWOT Framework: A Case Study of a Welding Services Small Enterprise - Bagus Dwi Romadhoni; Rita Mutiarni (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
Small and medium-sized enterprises (SMEs) in technical service sectors are required to continuously adapt to changing market conditions and increasing competitive pressure. Strategic planning is therefore essential to ensure business sustainability and competitiveness. This study aims to analyze the internal and external business environment of a welding services SME and to formulate appropriate development strategies using an integrated SWOT-based approach. A qualitative descriptive method was employed, with data collected through direct observation, in-depth interviews, and documentation. The analysis utilized the Internal Factor Evaluation (IFE) Matrix, External Factor Evaluation (EFE) Matrix, Internal–External (IE) Matrix, and the Grand Strategy Matrix. The results indicate that the enterprise possesses moderate internal strength and operates within a favorable external environment. The IE Matrix places the firm in a hold-and-maintain position, while the Grand Strategy Matrix identifies the firm in Quadrant I, indicating potential for growth-oriented strategies. Based on the SWOT Matrix, several strategic alternatives are proposed to enhance competitiveness and support long-term business development. This study highlights the relevance of integrated strategic analysis as a practical decision-making tool for SMEs in technical service industries.